E-059 Coil embolization of ruptured anterior communicating artery aneurysms: periprocedural complications. (4th July 2012) - Ding, D; Hilliard, J; Jensen, M; Evans, A; Dumont, A; Kassell, N; Kassell, N; Liu, K
Abstract : Introduction: Endovascular coil embolization of intracranial aneurysms has been proven to be safe and efficacious, withstanding side-by-side comparison to microsurgical clipping in multiple studies. Anterior communicating artery (ACOM) aneurysms comprise approximately 30% of all ruptured aneurysms and represent the most common site of rupture. There is no definitive data regarding the rate of thromboembolic and hemorrhagic complications associated with coil embolization of ruptured ACOM aneurysms. Our goals were to quantify the periprocedural rate of thromboembolic and hemorrhagic complications associated with coiling of ruptured ACOM aneurysms, identify aneurysm and treatment characteristics associated complications, and quantify the clinical outcomes following complications. Methods: We retrospectively reviewed our institutional neurointerventional database from 1999 to 2010 and identified all patients with ruptured ACOM aneurysms treated with endovascular intervention. Thromboembolic and hemorrhagic periprocedural complications were identified on post-procedural CT or MRI. We determined the modified Rankin Score (mRS) of the patients with complications at discharge. χ 2 test was used to determine the difference in rates of thromboembolic and hemorrhagic complications with respect to aneurysm diameter less than or at least 7 mm, single or non-single catheter coiling method, use of post-procedural oral antiplatelet therapy, use of immediate post-procedural heparin infusion and date of treatment before or after 2005. T-test was used to determine the difference in mRS between the thromboembolic and hemorrhagic complication groups. Results: Of the 419 patients presenting with aneurysmal subarachnoid hemorrhage, 123 patients harboring ruptured ACOM aneurysms were treated with endovascular coil embolization. There were a total of 22 periprocedural complications (17.9%) comprised of 18 thromboembolic (14.6%) and 4 hemorrhagic (3.3%) complications. Statistical analysis show significantly more thromboembolic than hemorrhagic complications (p=0.002). Diameter at last 7 mm (32.1% vs 9.5%), non-single catheter coiling method (16.7% vs 14.5%), use of antiplatelet therapy (18.8% vs 13.2%) and treatment after 2005 (15.5% vs 7.7%) were associated with higher rates of thromboembolic complications whereas diameter <7 mm (4.2% vs 0%), single catheter coiling method (3.4% vs 0%), no use of antiplatelet therapy (4.4% vs 0%), no use of heparin infusion (3.4% vs 0%) and treatment before 2005 (7.7% vs 2.7%) were associated with higher rates of hemorrhagic complications. However, only aneurysm size at least 7 mm had a statistically significantly higher rate of thromboembolic complications than size <7 mm (p=0.003). The mean mRS of patients with thromboembolic complications (3.5) was higher than that of patients with hemorrhagic complications (1.7) but not significantly different (p=0.084). Conclusions: In a large number of ruptured ACOM aneurysms treated by coil embolization, thromboembolic complications were found to be significantly more common than hemorrhagic complications. Thromboembolic complications were significantly higher in ACOM aneurysms with diameter at least 7 mm compared to those with diameter <7 mm. While hemorrhagic complications are generally more feared by interventionalists than thromboembolic complications, we found the clinical outcomes to be no different between the two groups. This suggests that we should perhaps be more aggressive with intraprocedural and post-procedural anticoagulation when considering endovascular treatment of ruptured ACOM aneurysms. Competing interests: None.